2001
DOI: 10.1046/j.1365-2583.2001.00236.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of ribosomal DNA polymorphisms discriminating among chromosomal forms of Anopheles gambiae s.s.

Abstract: The sequence of a 2.3 kb long DNA segment derived from the 5'-most end of the ribosomal intergenic spacer was determined in three chromosomal forms of Anopheles gambiae s.s. The analysis revealed that the sequence of the Mopti form differed from that of the Bamako and Savanna forms by a total of ten nucleotide substitutions. Using these sequence variations we set up a diagnostic polymerase chain reaction (PCR) assay to distinguish mosquitoes belonging to the three chromosomal forms, facilitating studies on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
259
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 257 publications
(263 citation statements)
references
References 16 publications
3
259
0
1
Order By: Relevance
“…A. gambiae (sensu strictu) has been distinguished into several different ecotypes on the basis of floating chromosomal inversions, whose prevalence varies geographically and seasonally, suggesting that they may ''lock in'' specific allelic combinations important for malaria transmission (35,36). More recently, a small number of molecular markers have also suggested the existence of flexibility and even mosaicism in the A. gambiae genome (37,38). The high level of polymorphism that we detected between BAC 8N20 and the Consensus Sequence is reminiscent of the human MHC locus, which encompasses at least 200 genes, most of which are highly polymorphic and have roles in immune responses (39).…”
Section: Discussionmentioning
confidence: 99%
“…A. gambiae (sensu strictu) has been distinguished into several different ecotypes on the basis of floating chromosomal inversions, whose prevalence varies geographically and seasonally, suggesting that they may ''lock in'' specific allelic combinations important for malaria transmission (35,36). More recently, a small number of molecular markers have also suggested the existence of flexibility and even mosaicism in the A. gambiae genome (37,38). The high level of polymorphism that we detected between BAC 8N20 and the Consensus Sequence is reminiscent of the human MHC locus, which encompasses at least 200 genes, most of which are highly polymorphic and have roles in immune responses (39).…”
Section: Discussionmentioning
confidence: 99%
“…Samples were further identified as belonging to the M/S molecular form according to the PCR protocol described in Favia et al (2001). Microsatellite DNA analysis was performed for 11 dinucleotide loci (GT repeats) and one trinucleotide locus (AGC repeat).…”
Section: Species Identification and Microsatellite Genotypingmentioning
confidence: 99%
“…They were initially described on the basis of several single nucleotide polymorphisms (SNPs) in the X-linked ribosomal DNA locus (7,8). Heterozygotes were rarely found in nature and studies of reproductive isolation (RI) confirmed strong assortative mating with interform matings occurring at a frequency of ∼1% (9).…”
mentioning
confidence: 99%